(untitled) (CIPEEX, 2025)
Introduction: Obstructive sleep apnea (OSA) exacerbates sleep disorders and is associated with chronic diseases. Bariatric surgery, in turn, promotes weight loss and improves OSA, reducing pressure on the airways. Objective: To evaluate the importance of treating obstructive sleep apnea as a preparatory step for the success of bariatric surgery in patients with severe obesity. Method: This study is an integrative literature review that searched for articles in the PUBMED, LILACS, and SciELO databases, using the descriptors "Morbid Obesity," "Bariatric Surgery," "Obstructive Sleep Apnea," and "Preoperative Period," associated with the boolean "AND." The method selected original, free studies from 2019 to 2024, in Portuguese or English, resulting in three articles. Result: The studies emphasized the treatment of OSA as essential for bariatric surgery, resulting in significant improvements in the apnea-hypopnea index (AHI) and body mass index (BMI). OSA was found in 38.2% of bariatric patients, increasing readmission and complication rates, especially in more obese patients and those over 40 years old. Conclusion: The treatment of OSA is crucial to prepare patients with severe obesity for bariatric surgery, improving respiratory function, reducing complications, and promoting weight loss and remission of comorbidities, which leads to a more positive prognosis.